KOMPETENSI KEPRIBADIAN YESUS SEBAGAI GURU MENURUT INJIL MATIUS - Nelly, Nelly; Tina Yoseva, Rut; Manno, Daud (Sekolah Tinggi Teologi Duta Panisal, 2026)
Personality competency is a personal ability that reflects a personality that is steady, stable, mature, wise and authoritative, being a role model for students, and having noble character. The focus of this research is Jesus' personality competence as a teacher according to the Gospel of Matthew. The method used is a qualitative approach with a type of library research supported by Bible exposition. The results obtained were that the personality competency that Jesus possessed was having good morality and spirituality: fear of God, love for others, holy living, integrity, having a stable soul, having the fruit of the spirit; have character: be a role model, have noble character, be steady and stable, pay attention to many people, mature attitude; had authority: His ministry was wonderful, fearless, of God; work creatively, innovatively and pray; and focus on the goal: commitment to the call, making all nations His disciples, carrying out the mission of the call.